Empowering women through targeting information or role models: Evidence from an experiment in agricultural extension in Uganda - Lecoutere, Els; Spielman, David J.; Van Campenhout, Bjorn (Elsevier, 2023)
Agricultural advisory services are generally biased towards men, with information targeted mainly to male members within the household, and in formats that often reinforce male dominance in agricultural decision-making. Such biases affect women’s ability to make informed decisions and limit their intra-household bargaining power. Because women’s empowerment in agriculture has many well-established benefits, designing inclusive agricultural extension and advisory services is important. In this study, we challenge the assumption that information is fully shared between co-heads of a household. We also test if portraying women as equally able farmers challenges gender norms and stereotypes in agriculture. We do this through a field experiment in eastern Uganda in which videos that provide information on recommended maize-farming practices are shown to monogamous maize-farming households. In the experiment, we manipulate who within the household is exposed to the information contained in the video. Furthermore, we vary the gender of the person delivering the information in the video. We find that targeting the female co-head alone with information increases her knowledge about recommended practices, her role in agricultural decision-making, her subsequent adoption of recommended practices and inputs, and yields on fields she manages, while the male co-head’s knowledge about the practices and his unilateral decision-making is reduced. When both co-heads are targeted, joint adoption of recommended practices and inputs increases, while the male co-head’s unilateral decision-making is reduced. We find some support that featuring female role models in the videos challenges men’s beliefs and stereotypes about women’s roles in agriculture, and encourages adoption of recommended practices by women. We conclude that if the aim is to empower women, most gains can be made by re-designing advisory services to target information exclusively to the female co-head within the household. Challenging gender stereotypes may create room for increasing women’s involvement in agriculture.